Kindler′s syndrome: A case series of three Indian children - Ghosh Sudip; Bandyopadhyay Debabrata; Das Jayasri; Chatterjee Gobinda; Sarkar Somenath (Wolters Kluwer Medknow Publications, 2010)
Kindler′s syndrome is a very rare genodermatosis characterized by acral blistering starting in infancy, photosensitivity, progressive poikiloderma, cutaneous atrophy, and various forms of mucosal involvement. A large number of other cutaneous and extracutaneous features have also been described. We report here three cases of Kindler′s syndrome from eastern India for the rarity of the syndrome and to emphasize the importance of considering this condition in the differential diagnosis of disorders that can cause blistering, cutaneous atrophy, and/or poikilodermatous skin changes.